E-Cash & E-Vouchers: The digitalization of the humanitarian aid and logistics - Loic Cohen; Vincent Salaun (Digitalization in Supply Chain Management and Logistics: Smart and Digital Solutions for an Industry 4.0 Environment. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 23, 2017)
In the recent years, the mobile phone coverage expansion and the more widespread use of cash cards have eased the implementation at scale of Cash and Vouchers (C&V) programmes in the humanitarian sector. Furthermore, the development of web-based interfaces, designed to respond to the specifics needs of the sector, supports the implementation of C&V programmes. Due to the technological innovations, C&V assistance is growing rapidly and the sector seriously considers the ''e-assistance' as an alternative to the in-kind assistance. This paper aims to investigate the potential impact of this digitalization on the humanitarian supply chain. If the literature states that C&V programming reduces cost, brings speed and serves better the needs of the beneficiaries, no real reference is made on the impact on the humanitarian supply chain. To explore this gap, the research uses the punctuated equilibria theory proposed by Eldredge and Gould (1972) and adapted for Management Sciences by several researchers such as Trushman and Romanelli (1985) or Rowe and Besson (2011). Having closes similarities with the humanitarian supply chain, a parallel is drawn with the event supply chain, which stands at a stage further in the integration of new technologies and has consequently re-shaped its structures and strategies. Through a qualitative methodology based on participant observations, institutional communications and secondary data, this paper highlights how C&V supported by digitalization has created a rupture in the role of the humanitarian logistics and how humanitarian organisations search to find a new equilibrium between strategy of intervention and supply chain strategy.
urn:nbn:de:gbv:830-88217534; 10419/209192; https://econpapers.repec.org/RePEc:zbw:hiclpr:23
Keywords: 650; humanitarian logistics; event logistics; Cash & Vouchers (C&V)